Vitamin D receptor gene polymorphisms are linked to and associated with adult height - Xiong, D-H; Xu, F-H; Liu, P-Y; Shen, H; Long, J-R; Elze, L; Recker, R R; Deng, H-W (Journal of medical genetics, 2005)
Background: The vitamin D receptor (VDR) gene is important to human stature, as it mediates metabolic pathways, calcium homeostasis, and phosphate homeostasis, which influence growth. Methods: We examined the relationship between VDR and adult height in 1873 white subjects from 406 nuclear families. Four SNPs, namely −4817A/G at intron 1, FokI C/T at exon 2 start codon, BsmI A/G at intron 8, and TaqI T/C at exon 9 in VDR were tested for linkage and association with adult height variation by the program QTDT (quantitative transmission disequilibrium test). The bT haplotype of the BsmI and TaqI loci was further tested for its association with height in unrelated samples randomly chosen from the 406 nuclear families by traditional population association methods. Results: All four tested SNPs were linked to adult height. Within family associations with height were detected at BsmI and TaqI loci (p = 0.048 and 0.039, respectively). Analyses based on BsmI/TaqI haplotypes also revealed evidence for linkage (p = 0.05) and association (p = 0.001) with height. The bT haplotype was significantly associated with higher adult height (p = 0.033, within family association test). Such an association might be female specific and influenced by menstrual status. Conclusions: Our results strongly suggest that VDR may be linked to and associated with adult height variation in white popuations.